Dinâmica hidrológica e avaliação do modelo GeoWEPP na predição da erosão hídrica em microbacias hidrográficas com diferentes usos no Cerrado - Magalhães, Wellington de Azambuja (2019)
The cultivable areas in the Cerrado have increased considerably in recent decades and some of the agricultural practices adopted have led to accelerated water erosion. Thus, it is essential to evaluate and calibrate and models that allow to efficiently predict the erosion process in crops. For this reason, the present work was developed with the objective of evaluating the water dynamics and determining the losses of soil and water in three watersheds; to evaluate the conditioning factors of modeling in the production of sediments at the micro-basin level using the GeoWEPP software. The basins selected for this study have representative uses of the main land use systems in the Cerrado biome: agriculture with soybean and corn cultivation (clayey Oxisol), extensive livestock farming and native vegetation (reference to an area not anthropized by Quartzene Neossol). To achieve the proposed objectives, soil losses estimated by the GeoWEPP model were compared to the losses measured in each of the micro-basins. For application of the GeoWEPP model, climatic and hydrological monitoring was carried out in each of the micro-basins, as well as the creation of input files in the WEPP model (climate, soil, land use and management and topography). A study was also carried out to characterize the study watersheds in terms of morphometry, pedology and topography. For the monitoring of water losses and sediment production, the identification of the point of convergence of surface waters was carried out in the three study basins, in which the structures for quantifying the flow and sediment production were installed. Finally, the model for the prediction of soil and water losses was applied through the integration of the GeoWEPP, TOPAZ and ArcView software. The results obtained allowed us to conclude that: The studied watersheds have a form factor below 1.0, giving an irregular and elongated shape, and less propensity to flooding. The microbasins with sandy texture soils showed greater regularity in the flow over the evaluated period and the microbasin with agriculture, with dominance of clay soil, presented greater extremes in the permanence curve and lower flow in the dry season. The average annual soil losses observed in the microbasins with agriculture, pasture and native vegetation are 0.11, 0.06 and 0.10 Mg ha-1 year-1 , respectively. The presence of vegetation cover with pasture and native vegetation contributes significantly to less soil loss in the basin of the microbasins. The GeoWEPP model performed better when the calibration parameters Ke, Ki, Kr and τc were inserted in the model, with good accuracy in estimating annual soil losses for pasture and native vegetation, both with sandy soils. The model underestimated the values of soil losses in the events in the microbasins with pasture and native vegetation, presenting results even less representative after the insertion of the parameters in the microbasin with agriculture.